Thiolactone-based polymers for formaldehyde scavenging coatings. (September 2016) - Resetco, Cristina; Frank, Daniel; Dikić, Tamara; Claessens, Sven; Verbrugge, Tom; Du Prez, Filip E.
Graphical abstract: Highlights: Functionalized UV-cured polymer coatings were prepared using thiolactone chemistry. Polymer coatings containing amines were effective in scavenging formaldehyde. Formaldehyde emissions from urea-formaldehyde adhesive were reduced by the coating. Abstract: A novel, straightforward chemical platform to prepare polymers with covalently bound amine functional groups has been developed for applications as coatings that scavenge formaldehyde emissions. For the polymer preparation, an amine-thiol-ene conjugation process was used to combine N-(allyloxy)carbonyl homocysteine thiolactone monomer with different amines, which simultaneously released a thiol group for subsequent thiol-ene radical polymerization. Results of the European standard formaldehyde release test by the flask method indicated that the obtained polymers with higher amine loadings resulted in a greater reduction in formaldehyde concentration. Urea-formaldehyde adhesive was overcoated with scavenging polymers, which resulted in a significant reduction in formaldehyde emissions. The amine-functionalized polymers were characterized by NMR and DSC before and after exposure to formaldehyde. After exposure to formaldehyde, polymers exhibited additional proton peaks in the NMR spectra and their glass transition temperature increased, which implied that formaldehyde was bound to the polymers.